1998
DOI: 10.1021/ac970852q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Reaction Dynamics in a Trypsin-Modified Capillary Microreactor

Abstract: Application of mild vibration to an immobilized trypsin capillary microreactor can enhance digestion rates for many globular and glycosylated proteins (12-70-kDa range) without additional sample handling. A sinusoid wave form generator and a simple piezoelectric transducer were used to apply vibration in a wide frequency range to the 50-μm-i.d. enzyme microreactor over its entire length. The mass transport properties of the microreactor were quantitatively examined for protein digestions through the use of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A solution-phase enzymatic assay was described by Wang [1], but this approach can yield autodigestion, and may require a delicate separation between the enzyme and the reaction products. The sorption or covalent coupling of enzyme molecules to the inner surface of capillary (microchannel) is possible [35], but is limited by the low specific inner surface of the capillary and the impossibility to renew the enzyme activity. This limitation was overcome by the immobilization of enzyme molecules to the surface of nano/microparticles [33,36].…”
Section: Introductionmentioning
confidence: 99%
“…A solution-phase enzymatic assay was described by Wang [1], but this approach can yield autodigestion, and may require a delicate separation between the enzyme and the reaction products. The sorption or covalent coupling of enzyme molecules to the inner surface of capillary (microchannel) is possible [35], but is limited by the low specific inner surface of the capillary and the impossibility to renew the enzyme activity. This limitation was overcome by the immobilization of enzyme molecules to the surface of nano/microparticles [33,36].…”
Section: Introductionmentioning
confidence: 99%
“…But the bioreactive probes are critical to reuse because of the loss of the enzymatic activity due to the rigorous washing tip process or the occupation of the active site of the proteases by the excessive matrix. Most reported microreactors are based on the format of microcolumns, that is, the enzyme is immobilized on support media [6,7], and then packed into the microcolumn, or onto the surface of silicon-based microfluidic chips [8,9] or on the fused-silica capillary directly by the covalent bonding method [10][11][12]. Compared with digestion of protein by the immobilized enzyme on probe tips, less analyte is needed for the mass mapping and the enzyme is reusable.…”
Section: Introductionmentioning
confidence: 99%
“…Licklider et al [10] reported the use of a capillary microreactor for protein digestion, followed by online ESI and off-line MALDI analysis. The microreactor is vibrated with an electric engraving tool to enhance reaction rates and reduce the digestion time to about 30 min [11]. Similarly, a thermal denaturation procedure can effectively accelerate the digestion of a protein by a capillary microreactor; by this method 9 fmol horse heart cytochrome c could be well characterized within 5 min [12].…”
Section: Introductionmentioning
confidence: 99%
“…Kuhr's group [31,32] later found that the proteolysis reaction rate could be enhanced by applying low-power acoustic vibration to the capillary, with digestion carried out in a batch-wise procedure. Efficient tryptic digestions of large proteins have been carried out in as few as 30 min [33]. The capillary microreactors were used for protein characterization by trypsin, pepsin and carboxypeptidase Y digestion.…”
Section: Immobilized Enzyme Reactorsmentioning
confidence: 99%